Quantifying Lithogenic Inputs to the Southern Ocean Using Long-Lived Thorium Isotopes - Pérez-Tribouillier, Habacuc; Noble, Taryn L.; Townsend, Ashley T.; Bowie, Andrew R.; Chase, Zanna (Frontiers in Marine Science, 2020)
Above the Kerguelen Plateau in the Southern Ocean, lithogenic inputs containing essential trace metals such as iron naturally fertilize surrounding waters, enhancing marine primary productivity. Quantifying trace metal inputs and their source is important for understanding bloom size, dynamics and variability, yet is challenging to accomplish in this dynamic environment. In this study, long-lived Th isotopes were applied to quantify the lithogenic supply from the Kerguelen Plateau to the Southern Ocean. The concentrations of 232Th and 230Th were measured using a novel pre-concentration method using the Nobias resin from 10 stations above and on the slopes of the plateau. Elevated 232Th/230Th ratios in the upper 500 m of the water column confirm the input of lithogenic material from islands, glaciers and the resuspension of shelf-deposited sediments. 230Th concentrations were used to calculate a scavenging residence time for Th, which was then applied to calculate the flux of dissolved 232Th required to match the observed concentrations of dissolved 232Th. Then, using the 232Th content of the lithogenic material from the Kerguelen Plateau and the solubility of Th reported in the literature, a flux of lithogenic particles was estimated. This flux ranged from 7 to 810 mg m-2 day-1 and is comparable to fluxes obtained using sediment traps (8 – 777 mg m-1 day-1) in other continental-margin zones of the Southern Ocean. A flux of iron was also calculated (716 - 2,220 nmol m-2 day-1) based on the amount of iron with respect of thorium in the material from the Kerguelen Plateau and considering a similar long-term solubility of both elements. These results also match with previous budgets generated for the region (188 - 3,722 nmol m-2 day-1). This study confirms the utility of long-lived Th isotopes to quantify lithogenic inputs from continental margin settings.